2016
DOI: 10.1007/s00125-016-4175-1
|View full text |Cite|
|
Sign up to set email alerts
|

Chronomedicine and type 2 diabetes: shining some light on melatonin

Abstract: In mammals, the circadian timing system drives rhythms of physiology and behaviour, including the daily rhythms of feeding and activity. The timing system coordinates temporal variation in the biochemical landscape with changes in nutrient intake in order to optimise energy balance and maintain metabolic homeostasis. Circadian disruption (e.g. as a result of shift work or jet lag) can disturb this continuity and increase the risk of cardiometabolic disease. Obesity and metabolic disease can also disturb the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 174 publications
(244 reference statements)
1
59
0
4
Order By: Relevance
“…Suppression of melatonin secretion by pinealectomy abolished the blood glucose circadian rhythm in rats under a non-circadian scheduled feeding regimen without altering blood insulin levels (la Fleur et al, 2001b). Pinealectomy impaired glucose tolerance, which could be corrected by exogenous melatonin administration (Forrestel et al, 2017). The chronic melatonin administration was shown to improve insulin sensitivity and ameliorate obesity in some animal models (Agil et al, 2013; Nduhirabandi et al, 2011), but was also shown to cause glucose intolerance in other studies (Cagnacci et al, 2001; Rubio-Sastre et al, 2014).…”
Section: Hormones and Neuropeptides In Metabolic Functions Of The Cenmentioning
confidence: 99%
“…Suppression of melatonin secretion by pinealectomy abolished the blood glucose circadian rhythm in rats under a non-circadian scheduled feeding regimen without altering blood insulin levels (la Fleur et al, 2001b). Pinealectomy impaired glucose tolerance, which could be corrected by exogenous melatonin administration (Forrestel et al, 2017). The chronic melatonin administration was shown to improve insulin sensitivity and ameliorate obesity in some animal models (Agil et al, 2013; Nduhirabandi et al, 2011), but was also shown to cause glucose intolerance in other studies (Cagnacci et al, 2001; Rubio-Sastre et al, 2014).…”
Section: Hormones and Neuropeptides In Metabolic Functions Of The Cenmentioning
confidence: 99%
“…It is noteworthy that circadian disruption can increase the risk of CVD, diabetes, cancer, and metabolic syndrome [28,29]. In contrast, melatonin, a chronobiotic hormone, has been considered as a chronotherapeutic drug for these NCDs [28]. Additionally, several lines of evidence indicate that melatonin interacts with these proposed mechanisms contributing to programmed process.…”
Section: Mechanisms Of Developmental Programmingmentioning
confidence: 99%
“…In fact, because of its widespread production, melatonin acts in both endocrine and paracrine/autocrine manner. Furthermore, its effects have been shown in the cardiovascular and immune system, and on the regulation of metabolic functions (68). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, melatonin was found to inhibit cAMP levels and insulin secretion in INS-1 832/13 β-cells, and these effects were further enhanced in β-cells overexpressing MTNR1B (22). Of note, melatonin is a prescription drug for improving sleep and for jet lag (8); therefore, it should be carefully administered in individuals with sleep disturbances, particularly in obese patients and carriers of the MNTR1B risk allele. However, administration of melatonin has been shown to improve sleep quality independently of rs10830963 genotype, despite the negative effect on insulin secretion (22).…”
Section: Introductionmentioning
confidence: 99%